The Art of Not Stopping: Grit Among the Breadwinner Senior Citizens in Pilar, Bataan - Jayvie Villazor (Indonesian Journal of Global Health Research, 2025)
Approximately fifty percent of elderly individuals in the Philippines are currently employed. A significant number of them are exposed to health hazards and have a low socioeconomic level despite having worked for a considerable number of years. The current study aims to provide a detailed account and analysis of the core essence of the experience of breadwinner senior citizens as they strive to maintain their grit for numerous years. The findings revealed four themes, or 4K of grit, namely: keep on, keep at, keep up, and keep growing. Each theme generated subthemes that further elaborated on the experiences of breadwinner senior citizens. Keep on is divided into five subthemes: familial’s sake, financial autonomy, fortitude in the past, and founding leisure. Keep at is divided into two themes, namely the personification of aging and perceived hardships. Meanwhile, the keep-up had four subthemes: guarding the mind, being God-centered, getting support, and having greater focus in the body. Lastly, the keep growing is composed of two themes the steadfastness in work and senescence’s’ joy. While the participants have shown resilience in the face of several challenges, it is strongly recommended that local government agencies improve and closely supervise the current program and activities aimed at addressing the financial difficulties as well as the physical and mental difficulties of the breadwinner senior citizens. More so, the said research will add additional fund of knowledge in the field of gerontology and psychology in the Philippines.